AKUNTANSI PARTAI POLITIK - Kariyoto, Kariyoto (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
Accounting for Political Parties. Healthy political parties, credible and capable of running the General Election held in a democratic, honest and fair is the capital of democracy credible. Democracy is a credible government authorized the creation of a solid and authoritative with effective control of the institution legistalif. Credible democracy is not possible without transparency and clear accountability mechanisms for the financing of political activities, both financial and political party financing of the General Election. This financial accountability requires transparency of financial accounting standards for political parties, political party auditing guidelines, and the existence of guidelines, regulations, and procedures for financial reporting on the activities of the General Election campaign for political parties. One of the major problems that arise are the accounting standards. In the meantime, the existing accounting standards, namely Principle of Financial Accounting Standards 45, the accounting standards made for non-profit organization that Indonesia Institute of Accountants (IAI )is also used for political parties. (PSAK) 45 is not sufficient to accommodate the characteristics of different political parties with other nonprofit organizations. Therefore, this study recommends a modification or specific guidelines for financial accounting standard for political parties. This article we hope will encourage various parties, in this Parliament, the Commission, the Supreme Court and the Association of Accounting Indonesia to sit together and agree on specific accounting standards for political parties including campaign funds. This paper hopefully be a reference, although subject to change according to the Law on Political Parties and Elections are currently being discussed in Parliament. Accounting standards in this paper can be a reference to the new legislation. Reflecting the general election of 2009 was the lack of management, accountability and control of financing of political activities. Almost all political parties having problems financing of political activities, including the financing of legislative elections that followed the political campaign. Weak financial systems has led to uncontrolled political money (money politics), which involves Â almost all political parties in elections.